Diagramming Duration : Bergsonian Multiplicity and Chaos Theory - Harris, Paul (Intermédialités / Intermediality, 2004)
This essay traces Bergson's search for a language adequate to express the notion of “durée réelle” as a continuous multiplicity, in his work “Introduction à la métaphysique.” It then argues that computer-graphic images of chaos theory in fact provides such a language, and develops the conceptual and theoretical implications that follow from this correlation.